Persistence and resistance: survival mechanisms of Candidatus Dormibacterota from nutrient‐poor Antarctic soils. (3rd June 2021) - Montgomery, Kate; Williams, Timothy J.; Brettle, Merryn; Berengut, Jonathan F.; Zhang, Eden; Zaugg, Julian; Hugenholtz, Philip; Ferrari, Belinda C.
Summary: Candidatus Dormibacterota is an uncultured bacterial phylum found predominantly in soil that is present in high abundances within cold desert soils. Here, we interrogate nine metagenome‐assembled genomes (MAGs), including six new MAGs derived from soil metagenomes obtained from two eastern Antarctic sites. Phylogenomic and taxonomic analyses revealed these MAGs represent four genera and five species, representing two order‐level clades within Ca . Dormibacterota. Metabolic reconstructions of these MAGs revealed the potential for aerobic metabolism, and versatile adaptations enabling persistence in the 'extreme' Antarctic environment. Primary amongst these adaptations were abilities to scavenge atmospheric H2 and CO as energy sources, as well as using the energy derived from H2 oxidation to fix atmospheric CO2 via the Calvin–Bassham–Benson cycle, using a RuBisCO type IE. We propose that these allow Ca . Dormibacterota to persist using H2 oxidation and grow using atmospheric chemosynthesis in terrestrial Antarctica. Fluorescence in situ hybridization revealed Ca . Dormibacterota to be coccoid cells, 0.3–1.4 μm in diameter, with some cells exhibiting the potential for a symbiotic or syntrophic lifestyle.